CIRCUIT LEARNING MODEL-BASED HIGHER ORDER THINKING SKILLS TO IMPROVING STUDENTSâ PROBLEM SOLVING - Rosaini, Rosaini; Budiyono, Budiyono; Pratiwi, Hasih (Journal on Mathematics Education)
The 2013 curriculum emphasizes the application of Higher Order Thinking (HOTS) questions in learning, and it is also necessary for teachers to use student learning models. Teachers as supporters of both aspects mentioned need to be given attention because of difficulties applying the model of learning and hots in learning mathematics. This is due to the unfamiliarity of students with HOTS type questions in the learning model. The purpose of this research is to know the effectiveness of the HOTS-based learning model in facilitating the problem-solving ability of the students. The research subject is the seventh-grade student of SMP in Sleman, Yogyakarta. The result of this research is there is a change when using HOTS-based circuit learning in mathematics learning. The results of this study indicate that students pretest and posttest results are increasing, meaning that students completion abilities increase after using HOTS-based circuit learning model.